Charged quantum Oppenheimer–Snyder model - S. Habib Mazharimousavi (European Physical Journal C: Particles and Fields)
Abstract In the framework of loop quantum cosmology, particularly within the quantum Oppenheimer–Snyder model, the semiclassical Ashtekar–Pawlowski–Singh (APS) metric is associated with a static, spherically symmetric black hole that incorporates quantum effects derived from the APS metric. This quantum-corrected black hole can be interpreted as a modified Schwarzschild black hole, where the Schwarzschild metric function is adjusted by an additional term proportional to $$\frac{M^{2}}{r^{4}}$$ M 2 r 4 , with r denoting the radial coordinate and M,  the black hole mass. In this study, we show that such a quantum-mechanically modified black hole can arise in the context of nonlinear electrodynamics with either electric or magnetic charge. This charged, quantum-corrected solution is then matched to a dust ball of constant mass $$M_{APS}$$ M APS , governed by the APS metric, at a timelike thin-shell possessing nonzero mass m and electric charge Q or magnetic charge P. Analytically, it is demonstrated that the thin-shell oscillates around an equilibrium radius $$r=R_{eq}$$ r = R eq , which is expressed in terms of $$M_{APS}$$ M APS , m, and Q or P.